Knowledge, Attitude and Awareness of HPV Vaccination among College-Going Girls (18–26 years) in Delhi NCR - Rakheja, Shashi; Mehta, Diksha; Aggarwal, Indu; Goel, Harmeet; Joseph, Dona; Jain, Jyoti; Deep, Gagan; Grover, Muskan; Verma, Prerna; Singh, Brijesh (Asian Pacific Journal of Cancer Nursing, 2025)
Objective: This study aimed to evaluate the knowledge, attitude, and awareness (KAA) regarding HPV vaccination among college-going girls aged 18–26 years in Delhi-NCR, focusing on identifying barriers to vaccine uptake and factors influencing vaccination status. Methods: A cross-sectional survey was conducted between July 2024 and January 2025, involving 506 college students from various institutions in Delhi-NCR. Data were collected using an online structured questionnaire addressing demographics, knowledge of cervical cancer and HPV, awareness of the HPV vaccine, and attitudes toward vaccination. The responses were analyzed using descriptive statistics and chi-squared tests to assess associations between awareness and vaccination status. Results: Among the respondents, 80.2% correctly identified cervical cancer as a malignancy of the cervix, but 20% mistakenly associated it with other cancers like neck or bone cancer. Only 58.3% accurately recognized HPV as a virus linked to cancer, while a significant proportion confused HPV with HIV/AIDS (37.2%) or considered it a bacterial infection (16.6%). Despite 51% of participants being aware of the HPV vaccine, only 11.9% reported receiving it. Social media emerged as the most common information source (98%). Financial constraints (48%) were identified as the most significant barrier to vaccination, followed by a lack of awareness (40%) and safety concerns (12%). Social stigma also played a role, with many respondents finding it difficult to discuss HPV vaccination with their families. Conclusion: The findings reveal substantial knowledge gaps and socio-cultural barriers to HPV vaccination among college-going girls in Delhi-NCR. While awareness of cervical cancer was moderate, misconceptions regarding HPV and its vaccine persist. To increase vaccination coverage, it is crucial to implement educational campaigns targeting young women, address misinformation on social media, and advocate for the inclusion of the HPV vaccine in the National Immunization Programme. Reducing financial barriers through policy interventions could further enhance vaccine uptake.